Modeling Anisotropic Signature of Slab‐Induced Mantle Plumes From Thermochemical Piles in the Lowermost Mantle - Poulami Roy; Bernhard Steinberger; Manuele Faccenda; Michaël Pons (Geophysical Research Letters)
Abstract Seismic anisotropy, observed in the lowermost mantle near Large Low‐Shear‐Velocity Provinces (LLSVPs), is likely caused by strong deformation from mantle flow interacting with these regions and/or plume formation. This study explores slab‐induced plume generation from LLSVPs under the assumption that LLSVPs are thermochemical piles and resulting flow behavior using 3‐D regional‐scale mantle convection models in ASPECT, coupled with mantle fabric simulations in ECOMAN. We tested various models with different LLSVP density and viscosity. The modeling of the crystallographic‐preferred orientation with predominant activity of the slip system [001](100) for Bridgmanite and [100](001) for post‐Perovskite reveals that substantial seismic anisotropy develops in the lowermost mantle, and specifically (a) at the margins of the rheologically stiffer LLSVP piles where deformation and upwelling of the surrounding mantle take place and fast horizontally polarized shear waves (Vsh) transition to fast Vsv and (b) within plume roots and conduits where vertically polarized shear waves (Vsv) are faster.